Melanie Stryder’s Existence in Stephenie Meyer’s The Host (LITERA KULTURA : Journal of Literary and Cultural Studies, 2017)
Abstrak Tesis ini bertujuan untuk mengungkapkan eksistensialisme dalam karakter utama di novel Stephenie Meyer berjudul The Host, Melanie Stryder. Tesis ini membahas tentang bagaimana Melanie menampilkan eksistensialisme dan apa dampak dari keberadaan Melanie untuk hidupnya, cinta, dan dunia. Melanie yang hidup di era di mana alien menginvasi bumi harus mempertahankan keberadaannya sebagai manusia. Melanie hidup sebagai buronan, bepindah dari satu ke tempat lain untuk bersembunyi dan membuat saudaranya aman. Melanie memilih lebih baik mati daripada ditangkap oleh para pencari. Sebagai manusia dan mempertahankan keberadaannya, Melanie memiliki motif dalam setiap kegerakannya. Berpikir tentang apa dan bagaimana hidup sebagai ada manusia. Menjadi seperti manusia terkahir di bumi membuat Melanie harus siap kabur kapan saja, kesepian tanpa teman dan selalu dilingkupi kecemasan. Sebagai manusia, Melanie juga memiliki kebebasan untuk memilih, dia memiliki kehendak bebas untuk berakhir hidupnya atau tetap hidup bahkan ketika "jiwa" telah dimasukkan ke tubuhnya. Dengan Jamie sebagai satu satunya keluarga yang tersisa, Melanie tumbuh menjadi wanita yang bertanggung jawab penuh untuk memastikan Jamie selalu aman. Melanie juga menunjukkan dari bagaimana dia dalam kesadaran dan ketidaksadaran untuk dirinya sendiri. Konsep existenliasm dan Being dan Nothingness oleh Jean Paul Sartre digunakan untuk mengungkapkan tentang Eksistensialisme Melanie di novel Stephenie Meyer, The Host. Novel Host sebagai data utama akan disertai dengan data tambahan untuk penelitian mendalam dari penerapan teori tersebut. Hasilnya akan menunjukkan bagaimana Melanie sebagai eksistensialis dan dampak terhadap kehidupan, cinta dan dunianya. Kata kunci: existetialism, existenliast, kesepian, kecemasan, kebebasan, tanggung jawab, mobile, motif. Abstract This thesis intends to reveal existentialism in the main character of Stephenie Meyer’s The Host, Melanie Stryder. This thesis discussed problem concern in how Melanie represent existentialism and what the impact of Melanie’s existence to her life, love, and world. Melanie that is live in a era where aliens invaded the earth has to maintain her existence as a human. Melanie live as a fugitive, nomadic from one to another place to hide and make her brother safe. Melanie, she rather die than to be caught up by the seeker. As a human and maintain her existence, Melanie has her motif upon her mobile. Thought about what and how to life as exist human being. Seems like the last human being and a fugitive that has to nomad anytime, makes Melanie feels Loneliness and anxiety like common existence character. As a human Melanie also has her freedom to choice, she has free will to end up her life or keep alive even a “soul” has been inserted to her body. Having a litle brother to protect, build up Melanie to be fully responsible woman to make sure her brother save. Melanie also shows off how she is being for herself and in herself. The concept of existenliasm and Being and Nothingness by Jean Paul Sartre is used to disclose about Melanie’s Existentialism in Stephenie Meyer’s The Host. The novel The Host as the main data will be accompanied by additional data in order to eleborate deeply from the application of the theory. The result will be shown how Melanie as an existentialist and its impact to her life, love and world. Keywords: existetialism, existenliast, loneliness, anxiety, freedom, responsibility, mobile, motif.